Evaluation and Impact Factors of the Mechanical Properties of Phloem Bundle Fibers Obtained from Kenaf Germplasm. Issue 2 (4th March 2018) - Cheng, Zhou; Jin, Guanrong; Huang, Siqi; Zhu, Yunguo; Li, Shan; Xie, Xueyun; Li, Defang
ABSTRACT: The mechanical properties of kenaf phloem bundle fibers are valuable for reinforced composites or boards, more so than similar materials also used in textile or papermaking applications. 55 kenaf germplasm studied here showed an average phloem bundle fiber tensile strength of 643.6 MPa and an average elastic modulus of 23.3 GPa after chemical retting treatment. 19 of these kenaf germplasm had fiber tensile strengths >700 MPa, which can be attributed to intensive breeding programs. The fiber tensile strength and elastic modulus of kenaf germplasm had a significant positive correlation, but there was no such correlation between a fiber's mechanical properties and its diameter or agronomic characteristics. Among 56 hybridized combination F1 generations, the highest tensile strength was 928.3 MPa from a combination of No.30 of Xinan Wuchi × Guatemala 4. Therefore, breeding and screening are both useful for improving the mechanical properties of kenaf phloem bundle fibers. However, the effects of the used bundle fiber preparation method or cultivation year on the fiber's mechanical properties were more pronounced than those of the type of kenaf germplasm or breeding operation used. The mechanical properties of kenaf phloem bundle fibers treated by chemical retting were superior to those treated using natural retting.